Estudo comparativo da transmissão da luz, impacto térmico e sensibilidade dolorosa em tendão calcâneo de humanos entre três diferentes dispositivos de terapia de fotobiomodulação disponíveis no mercado - Melo, Fernando Hess Câmara (2020)
The use of PBMT has been favorable in the tendon repair process. Although several studies attest to the beneficial effect of PBMT on tendinopathies, only a few studies the penetration of light in situ, but in vitro and with immediate penetration measurements. Therefore this study aims to investigate the penetration time profiles of three different PBMT devices in the human Achilles tendon in situ during 150 seconds of exposure. One is a Class 4 device, with a Mean Power Output (MPO) of 9000 mW. The second is a Class 3B, with an MPO of 100mW. The third device is a Class 1M, with an MPO 450mW. To this end, a cross-sectional study was conducted in which 18 healthy volunteers were recruited in order to perform tests, with the tendon in relaxed condition. In the trial the collections were performed with the volunteer lying down, the Achilles tendons (right and left) previously marked and with the ultrasound images already acquired to measure the thickness of the skin, tendon and skin joint, thereafter the volunteers received the PBMT. The spot of the device will be in contact with the skin, in the lateral region of the ankle. Penetrating energy skin to skin was measured by an optical power meter on the medial face of the ankle after 150 seconds of irradiation. The right and left Achilles tendons of the volunteers were irradiated sequentially. The same procedure was performed for the three devices, with proper specifications offered by the manufacturer. The results offered a warning difference between the devices in energy absorption, availability and painful feel, prior to the heat on the skin tissue irradiated.